Original researchVascular endothelial growth factor in children with cyanotic and acyanotic and congenital heart disease - Baghdady, Yasser; Hussein, Yasser; Shehata, Mohamed (Archives of Medical Science, 2010)
Introduction: Vascular endothelial growth factor is a potent stimulator of angiogenesis. Children with cyanotic congenital heart disease often experience the development of widespread formation of collateral blood vessels, which may represent a form of abnormal angiogenesis resulting in increased morbidity and mortality. We undertook the present study to determine whether children with cyanotic congenital heart disease have elevated serum levels of vascular endothelial growth factor compared to children with acyanotic heart disease. Material and methods: Serum was obtained from 35 children with cyanotic congenital heart disease and 30 children with acyanotic heart disease. Vascular endothelial growth factor levels were measured in the serum of these patients by sandwich enzyme immunoassay. Results: Vascular endothelial growth factor was significantly elevated in children with cyanotic congenital heart disease compared to children with acyanotic heart disease (150.3 ±48.1 vs. 85.4 ±18.7 pg/ml, respectively, p < 0.001). In the cyanotic group, oxygen saturation (SaO2) was negatively correlated with VEGF (r = –0.631, p < 0.001) while haemoglobin was positively correlated (r = 0.781, p = 0.007). No significant correlations were found in the acyanotic group. Conclusions: Children with cyanotic congenital heart disease have elevated systemic levels of vascular endothelial growth factor directly related to the degree of cyanosis (SaO2 and haemoglobin levels). These findings suggest that the widespread formation of collateral vessels in these children may be mediated by vascular endothelial growth factor.